Die Familie angesichts der Migration im Lichte der Botschaften von Johannes Paul II. zum Welttag der Migranten - Ireneusz Stolarczyk (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2011)
The author of this article presents migration as a social phenomenon, which constitutes a challenge for both the international community and particular countries. The involvement of the Holy Father John Paul II, as well as the variety of problems featuring in messages for the World Day of Migrants allow the reader to perceive the issues connected with migration as extremely urgent - both for individuals and for communities, among which the family is of greatest importance. The reason why the Holy Father committed himself to this fi eld was to uphold human dignity and a global social solidarity. The analysis of this phenomenon allows the Holy Father to address a call for responsibility to various groups whose integral activity can make the phenomenon of migration more digni fi ed. The messages of the Holy Father also offer a direct invitation to all people of goodwill to make their own contribution so that every person and family are respected and discriminations that undertime human dignity.